2008
DOI: 10.1038/mi.2007.5
|View full text |Cite
|
Sign up to set email alerts
|

High frequencies of polyfunctional HIV-specific T cells are associated with preservation of mucosal CD4 T cells in bronchoalveolar lavage

Abstract: The mechanisms underlying the massive gastrointestinal tract CD4 T-cell depletion in human immunodeficiency virus (HIV) infection are not well understood nor is it clear whether similar depletion is manifest at other mucosal surfaces. Studies of T-cell and virus dynamics in different anatomical sites have begun to illuminate the pathogenesis of HIV-associated disease. Here, we studied depletion and HIV infection frequencies of CD4 T cells from the gastrointestinal tract, bronchoalveolar lavage (BAL), and blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 49 publications
6
80
2
1
Order By: Relevance
“…Another study found no depletion of CCR5 1 memory CD4 T cells in BAL from HIV-1-infected persons, compared with healthy controls (29). These authors argued that quantification of total CD4 cells is confounded by the inverted CD4/CD8 ratios at mucosal sites, such as the gut, compared with blood.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Another study found no depletion of CCR5 1 memory CD4 T cells in BAL from HIV-1-infected persons, compared with healthy controls (29). These authors argued that quantification of total CD4 cells is confounded by the inverted CD4/CD8 ratios at mucosal sites, such as the gut, compared with blood.…”
Section: Discussionmentioning
confidence: 98%
“…Additional conscious sedation with intravenous midazolam was given at the discretion of the operator. Standard flexible diagnostic bronchoscopy was performed, including a BAL of the middle lobe with 300 ml sterile saline instilled in 50-ml volumes as previously described (29). BAL fluid was stored on ice for a maximum of 30 minutes until bronchoalveolar lavage mononuclear cells (BALMC) were prepared as previously described (19), washed with phosphate-buffered saline, and strained through a 100-mm filter (Partec CellTrics; Partec Co., Mü nster, Germany).…”
Section: Bronchoalveolar Lavage and Blood Collection And Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…First and foremost, it is possible that a different "quality" of CD4 ϩ T-cell depletion in natural versus nonnatural SIV hosts at the intestinal mucosal level plays a major role. Indeed, both SIV-infected RM and HIV-infected persons experience a significant and preferential reduction of the IL-17-producing CD4 ϩ (Th17) and CD8 ϩ (Tc17) T-cell subsets throughout the gastrointestinal tract (81)(82)(83)(84). Similarly, the depletion of IL-17-producing innate lymphocytes in the GI tracts of SIV-infected Asian macaques has been demonstrated (85,86).…”
Section: Pathogenesis Of Hiv/siv-associated Microbial Translocationmentioning
confidence: 94%
“…The mucosal depletion of gut CD4 1 T cells does not appear to occur within the lung. In contrast, bronchoalveolar lavage (BAL) fluid from HIVinfected individuals early in infection has demonstrated higher numbers of CD4 1 T cells, which were also more polyfunctional, when compared with the terminal ileum (11). HIV-infected individuals, particularly in early-to mid-stage disease, have increased numbers of HIV-specific cytotoxic CD8 1 T lymphocytes within the alveolar space (12).…”
Section: Immunologic Abnormalities Associated With Hiv Infectionmentioning
confidence: 99%